Absolute quantification of VBNC state formation and resuscitation in alcohol-producing Klebsiella pneumoniae - Zhao, Shuo; Dou, Chenpu; Yang, Yang; Wang, Jiazheng; Li, Meng; Yang, Bin; Yuan, Jing; Zhang, Jian (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionMany bacterial species in the viable but non-culturable (VBNC) state pose a considerable risk to public health, primarily because of their ability to persist and resuscitate in the environment and their enhanced ability to escape detection. Our research revealed that high alcohol-producing Klebsiella pneumoniae (HiAlc Kpn) could cause non-alcoholic fatty liver disease. Notably, HiAlc Kpn is prevalent in the gut microbiome, and tracing pathogens in intestinal samples requires identifying and quantifying viable cells.MethodsFor precise quantification, we optimized PMA concentration between 5 μM and 200 μM and adjusted the incubation time from 5 to 30 minutes. Subsequently, we established real-time quantitative PCR (qPCR) and droplet digital PCR (ddPCR) methods to count HiAlc Kpn viable cells.ResultsThese methods produced methodological and technically comparable counts using KP, rpoB, and adhE. In mice fecal samples, we observed activity reductions ranging from 1.13 to 0.64 log10 DNA copies/mL. Interestingly, ciprofloxacin inhibited the recovery of VBNC-state cells while maintaining resuscitation and ethanol production after the removal of antibiotics in HiAlc Kpn, and we quantified the number of viable cells directly by PMA-ddPCR. This is a method for direct quantification that does not require an external standard curve reference.DiscussionThis is a method for direct quantification that does not require an external standard curve reference. This method could be an innovative tool for quantifying viable cells of K. pneumoniae, with potential applications in quantifying bacterial cells in the VBNC state, resuscitation, and assessing the persistence of pathogens in clinical samples.